A DAY OF GREAT ILLUMINATION: B. F. SKINNER'S DISCOVERY OF SHAPING - Peterson, Gail B. (Journal of the experimental analysis of behavior, 2004)
Despite the seminal studies of response differentiation by the method of successive approximation detailed in chapter 8 of The Behavior of Organisms (1938), B. F. Skinner never actually shaped an operant response by hand until a memorable incident of startling serendipity on the top floor of a flour mill in Minneapolis in 1943. That occasion appears to have been a genuine eureka experience for Skinner, causing him to appreciate as never before the significance of reinforcement mediated by biological connections with the animate social environment, as opposed to purely mechanical connections with the inanimate physical environment. This insight stimulated him to coin a new term (shaping), and also led directly to a shift in his perspective on verbal behavior from an emphasis on antecedents and molecular topographical details to an emphasis on consequences and more molar, functional properties in which the social dyad inherent to the shaping process became the definitive property of verbal behavior. Moreover, the insight seems to have emboldened Skinner to explore the greater implications of his behaviorism for human behavior writ large, an enterprise that characterized the bulk of his post‐World War II scholarship.